2020
DOI: 10.3390/ijerph17165919
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Behavior of General Practitioners for Generic Drugs

Abstract: The factors influencing General Practitioners’ (GPs) prescribing behavior are diverse in terms of health care policies and regulations, GPs’ education and experience, demographic trends and disease profiles. Thus, it can be useful to analyze the specific local patterns, as they affect the quality of healthcare and the stability of the healthcare market. The aim of the present longitudinal retrospective study is to investigate the prescription of generic drugs in a database of about 4.6 million prescriptions fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…While study results from Italy showed slight gender-related differences whereas female physicians were less likely to prescribe generics while compared to males. 29 This can also explain the association found in this study where females have lower odds when it comes to exclusive right to substitute medicines. There is a need to explore underlying factors to explore more about this association in Lebanon.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…While study results from Italy showed slight gender-related differences whereas female physicians were less likely to prescribe generics while compared to males. 29 This can also explain the association found in this study where females have lower odds when it comes to exclusive right to substitute medicines. There is a need to explore underlying factors to explore more about this association in Lebanon.…”
Section: Discussionmentioning
confidence: 64%
“…20,28 Many factors such as gender, sex, education level, specialty, years of experience can affect doctors' prescription as well as substitution of brands to generics by pharmacists. 29,30 Results of this study have demonstrated that in Lebanon age of the physicians as well as sex and years of practice are significantly associated to their prescription behavior in different situations. The age of a physician was significantly associated with the prescription of the generics to lower the medical costs, as prescription of generics for this purpose was more common among younger physicians while compared to physicians 50 years and older.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This insight can help guide strategies to understand what the patient really expects from a generic drug. On the other hand, understanding the views of doctors and health professionals is fundamental when it comes to defining more assertive strategies for prescribing and promoting these products [ 82 ]. The core of this issue is related to how companies could direct strategies to assess the risks associated with these products, making the product even more reliable for the target audience.…”
Section: Discussionmentioning
confidence: 99%
“…there is little gender difference in terms of prescribing Rx drugs, with female GPs slightly more inclined to prescribe fewer generic drugs than male GPs; and finally, in terms of diagnoses, generic drug prescriptions are concentrated in a specific area, related mainly to diseases of the circulatory and digestive systems. The prescription of generic drugs also depends on the different diagnoses, and additionally, when the number of prescribed drugs and/or the number of off-patent APIs is large, the market offer of generic drugs is also high (Tuncay et al, 2020).…”
Section: Tuncay Et Al Revealed That Gps Have An Increasing Tendency T...mentioning
confidence: 99%